Prometeo de Nikos Kazantzakis - Brncic Becker, Carolina (Byzantion Nea Hellás, 2015)
In this essay about the dramatic trilogy Prometheus by Nikos Kazantzakis, it is analysed the recreation of myth as an esthetic resource allowing the author to show an existencialist conception of life. For that purpose a dialogue is established with the Aeschylos’s tragedy who is the first poet to resort to this myth in a dramatic play.Then we analysed the reappropiation of myth carried out by Kazantzakis on the basis of an individual proposal, that describes an existencialist vision of man and life.